Революційна картина світу в поезії панфутуристів (на матеріалі «Жовтневого збірника») - Довіна, Марина; Dovina, Marina (Східноєвропейський національний університет ім. Лесі Українки, 2014)
Статтю присвячено поетико-стилістичному та ідейному аналізу «Жовтневого збірника панфутуристів». Доведено, що у збірці реалізовано принцип еструкції: ідеологічний запит відображений на ідейному рівні, а особливості естетичної платформи – на поетико-стилістичному. З’ясовано, що Жовтень, електрика, місто, творчість стали основними категоріями моделювання революційної картини світу в поезії футуристів. The article is devoted to poetic, stylistic and ideological analysis of “October Panfuturists’ Collection”. The author argues that estruction principle is implemented in the collection: state request is realized on the ideological level, and the features of the aesthetic platform – on the poetic and stylistic level. The idea of man’s post-revolutionary rehabilitation by means of changing his social role from military to productive is approved in Futurists’ poetry. The process of total mechanization and its apogee – the human’s victory over elemental nature – are emphasized in Futurists’ revolutionary world view. It was found that October, electricity, city, creativity became basic categories of modeling Futurists’ revolutionary world view.
Revolutionary World View in Panfuturists’ Poetry: Case of “October Collection”
Keywords: футуризм; еструкція; революційна картина світу; Жовтень; futurism; estruction; revolutionary world view; October